The role of electronic media in the region in updating cultural codes and forming a complex of identities of the population (the case of Maikop television) - A. M. Siyukhova (Вестник Майкопского государственного технологического университета, 2024)
The issue of preserving cultural codes in ethnic communities in the era of globalization is relevant. The departure of a greater share of social interactions into the digital information space raises the need to include elements of traditional forms of culture in it in order to preserve and strengthen the ethnocultural identity of communities, especially in multi-ethnic regions. The most effective means of transmitting and assimilating cultural codes as the basis of identity, both among members of local sociocultural communities and among the larger society of the Russian nation, are artistic practices. The goal of the research is to identify the role of electronic media in the region in updating cultural codes and forming a complex of identities of the population. The research method used was content analysis – a selection of television programs about artistic practices over a certain time period, followed by classification and generalization. It was revealed that the main form of representation of artistic life are fragments of news blocks relating to exhibitions, festivals, competitions, theatrical performances, etc., which presented: a display of the traditions of folk art of local residents – the Circassians, the Cossacks, the Russians; coverage of artistic events with heroic and patriotic content; a story about involving children in activities in the field of academic art (sculpture, music). Taken together, a picture emerges of a stable system of artistic life in the region, within which an environment is formed for the preservation of cultural codes and a harmonious balance of ethno-local and national identity.